Effect of Prior Information on Bayesian Membership Calculations for Nearby Young Star Associations. Issue Volume 10:Issue S314(2015) (November 2015) - Lee, Jinhee; Song, Inseok
Abstract: We present a refined moving group membership diagnostics scheme based on Bayesian inference. Compared to the BANYAN II method, we improved the calculation by updating bona fide members of a moving group, field star treatment, and uniform spatial distribution of moving group members. Here, we present the detailed description of our method and the new results for Bayesian membership calculation. Comparison of our method with BANYAN II shows probability differences up to 90%. We conclude that more cautious consideration is needed in moving group membership based on Bayesian inference.